An index reflecting mesoscale vortex–vortex interaction and its diagnostic applications for rainstorm area - Yongren Chen; Yueqing Li; Lan Kang (Atmospheric Science Letters, 2019)
Abstract The Tibetan Plateau Vortex (TPV) and Southwest China Vortex (SWCV) are important precipitation systems of the upper reaches of the Yangtze River in China in the warm half year (May–October). Sometimes, the vortices both move towards the Sichuan Basin, and encounter one other to merge into a deep vortex that induces mesoscale convective systems (MCSs) and heavy rainfall. In this paper, a formula for the depth of the positive vorticity column (PVC) in two extreme rainstorm events was constructed to reveal the dynamical characteristics of TPV–SWCV interaction. The results showed that: (a) One feature of TPV–SWCV interaction was to form a deep vortex with very deep positive vorticity in the vertical direction, and the occurrence of extreme rainstorms was closely related to the deep vortex. (b) The PVC depth can describe the thickness features of the deep vortex well: MCSs with low brightness temperature were observed in the area of >2 × 102 hPa PVC depth, and their frequent activities were the direct reason for the occurrence of extreme rainstorms. (c) The rainstorm areas were basically consistent with the area of large PVC depth, especially the area of 5–7 × 102 hPa PVC depth where 24‐hr accumulated precipitation reached 100 mm or more. The study indicates that the PVC depth can reflect the development of vortices in the vertical direction, and has the potential to be a valuable index for diagnosing heavy rainfall area.